D'Ri and I: A Tale of Daring Deeds in the Second War with the British. : Being the Memoirs of Colonel Ramon Bell, U.S.A. - Bacheller, Irving, 1859-1950 (Salt Lake City, UT : Project Gutenberg, 2004)
"D'Ri and I: A Tale of Daring Deeds in the Second War with the British" by Irving Bacheller is a historical novel written in the early 20th century. The book recounts the adventures of Colonel Ramon Bell, navigating through the rugged landscape of the early 19th-century North America amidst the backdrop of the War of 1812. Central to the narrative is the relationship between Ramon Bell and Darius, or "D'ri," a loyal and rugged companion, as they confront both the perils of the wilderness and the challenges posed by war. At the start of the narrative, we are introduced to the lives of Ramon Bell and his family as they journey westward to establish a new home, highlighting the hardships and simple joys of pioneering life. The opening portion showcases their tumultuous journey, including encounters with wildlife, the trials of camp life, and the character of D'ri, who is depicted as a rugged and resourceful man with a unique way of speaking. Their travels lead them through challenges typical of frontier life, such as dealing with wolves and preparing for potential confrontations. The initial chapters set the stage for a tale steeped in adventure and camaraderie, establishing a strong emotional foundation as the story unfolds in the context of both personal growth and the larger historical conflict. (This is an automatically generated summary.)
Release date is 2004-05-01
Produced by Al Haines. Thanks to Dave Maddock for the Lilypond work
Keywords: United States -- History -- War of 1812 -- Fiction